PREVALENSI NYERI NEUROPATIK PADA PASIEN DENGAN NYERI KANKER DI RSUPN DR CIPTO MANGUNKUSUMO DAN PKN RS DHARMAIS - Henry Riyanto Sofyan; Tiara Aninditha; Louis Kwandou; Jonathan Odilo; Rini Andriani (PERDOSNI, 2020)
Introduction: Cancer pain is one of the most common complications in cancer. As much as 30-50% of cancer patients experienced pain. Cancer pain patients have reported complaints of pain with a neuropathic component. Early diagnosis of neuropathic cancer pain has a clinical implication for patient management. However, the proportion of neuropathic cancer pain has not been studied in Indonesian population. Aim: The study was to get an overview of neuropathic pain prevalence among cancer pain patients in Cipto Mangunkusumo General Hospital and National Cancer Referral Dharmais Hospital. Methods: The design of this research was cross-sectional. The study was done in Cipto Mangunkusumo General Hospital and National Cancer Referral Dharmais Hospital in July-September 2019. The subjects in this research were adult cancer patients who consulted with the Department of Neurology. The data acquired were patient’s demography, cancer history, imaging, and pain assessment. PainDETECT questionnaire was employed to assess neuropathic pain. The data were processed and presented descriptively and analytically. Results: There were 57 subjects obtained in this research with average age of 45.91. As much as 31.6% subjects had neuropathic cancer pain. Breast cancer identified in 38.6% subjects. There were no differences of gender, age, cancer type, and pain intensity between subjects with and without neuropathic cancer pain. Radiating pain and subject with metastasis experienced neuropathic cancer pain more frequently. Discussion: The prevalence of neuropathic cancer pain in the Indonesian population is 31.6%. Radiating pain and patients with metastasis cancer tend to experienced neuropathic pain more frequently. Keywords: Cancer, Indonesia, neuropathic pain, prevalence